Performance Assesment of The Volleyball Match Againts The Kudus Sukun Badak Team in The 2023 Proliga Volleyball Competition - Subagio, Irmantara; Muhammad, Muhammad; Jimenez, Jose Vicente Garcia; Irsyada, Machfud; Hartoto, Setiyo; Hidayat, Taufiq (Faculty of Sport and Health Sciences, 2023)
This research aims to identify the strategies that led to the loss of the Sukun Badak Team in the 2023 Proliga volleyball competition. The type of research used is non-experimental with quantitative descriptive methods. The sample of the study consists of four top-ranked boy volleyball teams, namely Jakarta Lavani Allo Bank (JLAB), Jakarta Bhayangkara Presisi (JBP), Jakarta STIN BIN (JSB), and Surabaya Bin Samator (SBS), and one lowest ranked volley team namely Sukun Badak Club (KSB) at the 2023 Proliga competition. The instrument used is an adapted and modified observation guideline from the FIVB 2005 VIS that measures six playing skills: service, receive, set, spike, block, and dig. The analysis of the research data uses descriptive analysis. Statistic results show the lowest score on serving, setter, and attack techniques when Sukun Badak clubs face JLAB clubs. The number of deadly balls when attacking (kill) is also the least when facing JLab clubs. The conclusion is that three dominant strategies end in the defeat of the Sukun Badak club: service, setting, and attacking.